2021
DOI: 10.1182/blood-2021-151195
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Early Relapse for Patients with Multiple Myeloma through Machine Learning

Abstract: AK+NG eq. cont. Introduction Management of multiple myeloma (MM) improved dramatically in the last decade. However, prognosis is still poor for high-risk MM patients experiencing early relapse (ER) within 12 months after primary diagnosis. While some patients achieve long lasting remission with first-line triple combinations including immunomodulatory drugs (IMiDs) and proteasome inhibitors (PI) followed by high dose therapy plus autologous stem cell transplantation (ASCT), ER has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Algorithms such as Gaussian process regression and Random Forest have been applied to the datasets that consist of baseline clinical, biochemical, and/or gene expression data. Kubasch et al, for example, showed that the trained ML model based on Gradient Boosting Classification could predict early relapse of NDMM with 73% accuracy using four features like the first-year best response after frontline treatment 12 . Orgueira et al reported the ML-based personalized prediction of OS for six first-line treatments using 50 variables consisting of age, International Staging System (ISS) stage, serum β 2 -microglobulin level, type of the first-line therapy, and the expression of 46 genes 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Algorithms such as Gaussian process regression and Random Forest have been applied to the datasets that consist of baseline clinical, biochemical, and/or gene expression data. Kubasch et al, for example, showed that the trained ML model based on Gradient Boosting Classification could predict early relapse of NDMM with 73% accuracy using four features like the first-year best response after frontline treatment 12 . Orgueira et al reported the ML-based personalized prediction of OS for six first-line treatments using 50 variables consisting of age, International Staging System (ISS) stage, serum β 2 -microglobulin level, type of the first-line therapy, and the expression of 46 genes 13 .…”
Section: Introductionmentioning
confidence: 99%